Chromium Carbonitride (CrCN) Coatings on SUS 316L with Potential Application as Bipolar Plate in PEMFC - Fawwaz Asri, Nur; Husaini, Teuku; Bakar Sulong, Abu; Herianto Majlan, Edy; Ramli Wan Daud, Wan; Abdul Razak, Bushroa; Afiqah Mohd Radzuan, Nabilah (International Journal of Engineering and Technology, 2019)
The effects of corrosion behavior and interfacial contact resistance (ICR) of sputtered chromium carbonitride (CrCN) on SUS 316L are investigated. The corrosion behavior of CrCN coatings as potential bipolar plates in proton exchange membrane fuel cells (PEMFCs) are studied by potentiodynamic tests in 0.5 M sulfuric acid (H2SO4) with a scan rate of 1 mV/S. The ICR values are measured to evaluate electrical conductivity. The surface topography and roughness are monitored by atomic force microscopy (AFM) to investigate the surface features of CrCN coatings that correspond to the X-ray powder diffraction (XRD) analysis. The diffraction peak of CrCN has a current density (Icorr) of 0.1 µA cm‒2 and ICR of 2.12 mΩ cm² at 80 ºC after the coated 316L is polarized. The formed metal nitrides and carbides possess prominent physical and chemical properties, such as superconductivity, high hardness, high melting points, high electrical conductivity and good corrosion resistance. Favorable factors are observed in CrCN of Sample C with 150 W and 80 min deposition that resists corrosion either at the anode or cathode side in the PEMFC. Coating materials using CrCN are proposed to improved bipolar plates, to achieve the single cell performance in PEMFCs.